Filsafat dan Sains dalam Pendidikan, Bimbingan dan Konseling - Wahidin, Wahidin (STKIP Muhammadiyah Pringsewu, 2017)
Abstract: Philosophy and science into light for the human civilization. Both have a different starting point, the philosophy developed using speculative-reflective approach, while science using deductive-inductive approach. Relations binding both like two sides of a coin. Philosophy gave birth to science and science contributed to philosophy. Besides, philosophy and science have the same goal of seeking the truth for the sake of the welfare of mankind. The results generated from both truths are relative and relative so that people will always explore, revise, and reconstructed the philosophy and knowledge that already exists, the goal is to find a new truth. Education and guidance and counseling is one branch of the ideas of philosophy and science. The goal of both is to develop human potential and to make a prosperous and happy human life. Oriented education in the process of making a man of what their condition becomes the condition of how it should be. Guidance and counseling as a branch of science education have different characteristics with education itself. The education process emphasizes the cognitive aspects of counseling and guidance while stressing the affective aspect. Making philosophy as a way of thinking and placing science as a way of knowing in education, guidance, and counseling is something mandatory so that the orientation and objectives of both can be achieved.Keywords: Philosophy, science, education, guidance, and counseling